ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI KUNJUNGAN PASIEN JKN DI POLI RAWAT JALAN RSUD DR. FAUZIAH BIREUEN - Riza Fahmi (Program Studi Ilmu Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Indonesia Timur, 2020)
In Indonesia, capitation funds for payment for health services are obtained from JKN participant premiums, which are partly a way of paying for health services through capitation. The research design uses a qualitative approach to identify the cause, by exploring what reality is happening at Dr. Fauziah Bireuen. The informants in this study consisted of key informants, namely 1 person in the outpatient and inpatient section and 1 nurse in the outpatient clinic and 6 patients in the outpatient clinic as the main informant. Data analysis techniques with data reduction, data presentation, and drawing conclusions / verification. The results showed that from 6 informants the average of their answers were: The location of the hospital was easy to access because the road was good using a vehicle with a distance of 1 hour so. Support of health workers is not optimal because often doctors are not in place and the services provided by nurses are still not friendly and communication is not effective and the provision of facilities and infrastructure is not optimal, it is necessary for hospital policies to provide infrastructure facilities that are not optimal. The tiered referral regulation is still a complaint from patients who think the referral is complicated because they cannot go directly to a public hospital, and nurses also assume that they feel disadvantaged because of the decrease in the number of patient. The conclusion obtained from the results of this study is that for the location of the hospital has been stepped by JKN participants, for the average health worker has not provided optimal services, for infrastructure availability is also not optimal and for the tiered referral system that is still running it makes it difficult for JKN patients to run. It is expected that there is still a need to pay special attention to indicators of service aspects which are still not optimally provided by doctors or nurses in serving patients so that service quality can be further improved.